Kewenangan Anak Tertua Dalam Pembagian Harta Waris (Studi Di Desa Bagendang Permai Kecamatan Mentaya Hilir Utara Kabupaten Kotawaringin Timur) - Dedy, Dedy (Jurnal Studi Agama dan Masyarakat, 2016)
The background of the authority Elder Son In Divisonof property inheritance at the village of Bagendang Permai district at MentayaHilir Utara of East Kotawaringin, the basis of the authority of Elder Son In Divison was entrusted to distributed the property inheritance at village BagendangPermai district of MentayaHilir Utara of East Kotawaringin, the implementation of the distribution